Effect of Commercial Bank Services on the Growth of Small and Medium Enterprises in Rwanda: A Case of Manufacturing Small and Medium Enterprises Bankrolled by Bank of Kigali - Mbabazi , Aline; Kengere, Osiemo Athanas (Journal of Finance and Accounting, 2023)
The general objective of the study was to investigate effects of commercial bank services on the growth of small and medium enterprises in Rwanda. Specifically, the study evaluated the effect of bank loan services on the growth of manufacturing small and medium enterprises in Rwanda, determine the effect of saving services on growth of manufacturing small and medium enterprises in Rwanda and identify the effect of financial literacy services on the growth of manufacturing small and medium enterprises in Rwanda. Located in Kigali’s Special Economic Zone, the branch of Bank of Kigali served as the site for the research. The study included both quantitative and qualitative methods. The research was done with small and medium-sized businesses who regularly utilize Bank of Kigali services. The study’s population consisted of 317 small and medium-sized manufacturing businesses that do business with Bank of Kigali and have checking accounts there. The study’s sample size was determined via the Solvin formula. Purposive sampling was used to pick a representative sample from the population to assure the validity of the results. Quantitative data on the relationship between commercial bank services and SME growth was gathered via a survey of 177 businesses. SPSS (Statistical Product and Service Solutions) was used for the analysis of the gathered data. There is a correlation between the three predictor variables (financial literacy services, saving services, and bank loan services) and the dependent variable (Growth of manufacturing SMEs of Bank of Kigali-Rwanda). Taking into consideration the total number of predictors, the modified R square value of 0.720 is calculated. Growth of manufacturing SMEs of Bank of Kigali-Rwanda results often differ from the projected values based on the model by an average of 0.34637, which is the standard error of the estimate. The results of an analysis of variance (ANOVA) suggest a significance level of 0.000<0.05, with F=130.431. This indicates the study’s author is certain that the study’s focus on financial literacy, savings, and bank loan services contributed to the expansion of Bank of Kigali-Rwanda’s manufacturing SMEs. The results showed a very significant positive link between Growth of manufacturing SMEs of Bank of Kigali-Rwanda and financial literacy, saving, and bank loan services (p< 0.05). Bank of Kigali should expand lending services with competitive rates, promote tailored savings products, and provide incentives for regular savings to support SME growth. Additionally, enhancing financial literacy programs through workshops and consultations will empower SMEs to make informed financial decisions, contributing to their success in Rwanda. Keywords: Commercial Bank Services, Growth of Small and Medium Enterprises, Bank of Kigali, Rwanda